A survey: dynamics of humanoid robots. (16th November 2020) - Sugihara, Tomomichi; Morisawa, Mitsuharu
Abstract : The mathematical foundation to describe the dynamics of a humanoid mechanism is reviewed. The discussion begins with the kinematics of an anthropomorphic mechanism, followed by the equation of motion of the system and the contact mechanics that accompanies with the motions. Some compact representations of both the robot dynamics and the contact mechanics are summarized. The former is referred to as the centroidal dynamics derived from the total momenta of the system, while the latter includes the contact wrench sum and the zero-moment point. They are naturally joined as a reduced-order dynamics model derived from an approximate relationship between the center of mass and the zero-moment point. Finally, some techniques to synthesize the intended motion into the joint actuation torques under limitations of contact forces are shown. This is basically a translation of a Japanese version with some modifications and reorganizations. GRAPHICAL ABSTRACT: UF0001